Lactic Acidosis: Pathophysiology, Diagnosis, and Nursing Management - Alsaleh, Sawsan Hussain Ali; Maryam Hussin Habib Alabood; Laila Eissa Abdullah Alatwan; Latifah Farhan Ahmed AlQasim; Eman Ali Khalifah Al Farhan; Sukinah Saleh Jasem Aljubran; Aisha Adel Abdulaziz Alsaqer; Hajer Saleh Yousef Alowaidh; Amal Rashed Fahed Alkhammash; Hind Nahar Hmad Alhagriaf; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Lactic acidosis is a critical metabolic condition characterized by the systemic accumulation of lactate, resulting from an imbalance between its production and clearance. It is commonly classified into Type A, caused by tissue hypoperfusion and hypoxia (e.g., shock), and Type B, associated with underlying diseases, toxins, or mitochondrial dysfunction. It is a frequent finding in critically ill patients and is strongly linked to high mortality rates. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to comprehensively review the pathophysiology, diagnosis, and management of lactic acidosis, with a specific focus on the integral role of nursing in early recognition, monitoring, and coordinating interdisciplinary care to improve patient outcomes. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The article synthesizes current medical knowledge on lactic acidosis, detailing its physiological mechanisms, risk factors, and diagnostic criteria. It outlines systematic approaches for assessment, evaluation (including arterial blood gas and anion gap analysis), and evidence-based medical and nursing interventions. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective management hinges on rapid identification and treatment of the underlying cause, such as infection source control in sepsis. Medical management involves goal-directed fluid resuscitation, vasopressor support, and optimizing oxygen delivery. Serial lactate monitoring and clinical assessment of perfusion are crucial for evaluating treatment efficacy. Nursing management is pivotal in executing these interventions, providing continuous monitoring, and ensuring coordinated, patient-centered care. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Lactic acidosis is a life-threatening condition requiring a prompt, systematic, and interdisciplinary approach. Successful outcomes depend on correcting the underlying cause, restoring tissue perfusion, and meticulous supportive care, with nurses playing a central role in monitoring, intervention, and care coordination.